Japan : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2001)
The paper provides an assessment of fiscal transparency practices in Japan against the requirements of the IMF code of good practices on fiscal transparency. The responsibilities of different levels of government, and of the separate branches of government, are well defined. The coordination and management of fiscal activity is fairly effective. There are many respects in which Japan meets high standards of fiscal transparency. Recent initiatives have improved fiscal transparency. There is nevertheless room for major progress in key areas.